Maison 22, Kawaguchi, Saitana : Kazuhiko Namba + Kai Workshop - Kaneko, Chikako (2002)
Vivienda industrializada con elementos metálicos, formado por un sistema de pórticos rígidos.
Keywords: JAPON; TOKYO; VIVIENDAS UNIFAMILIARES; ESTRUCTURAS; ESTRUCTURAS METALICAS; PREFABRICACION; INDUSTRIALIZACION; NAMBA, KAZUHIKO; KAI WORKSHOP